Constitutive modelling of sintering of 316L stainless steel microsize structures - Liu, Lin. (2013)
Constitutive model is useful to predict the final shape of sintered microsize structures. In this paper, the contribution of lattice diffusion (Nabarro-Herring creep) is considered and a constitutive model is established to simulate densification of 316L stainless steel microsize structures fabricated by micro metal injection molding. The predictive capability of the model is verified by comparing the theoretical calculations with the experimental results. The influences of boundary energy on modeling results are discussed. It is found that the modeling results agree reasonably well with the experimental results.